Analysis on the Lack of Motivation and Dropout in Engineering Students in Spain - Abdelhamid Tayebi; Josefa Gomez; Carlos Delgado (IEEE Access, 2021)
The dropout rate of engineering students is a concerning problem at the present time in many countries, resulting in difficulties to follow the demand of professionals in certain technological sectors as well as an associated negative economic impact. This study identifies a number of factors affecting the motivation degree of current electrical and computer engineering students, as well as the main reasons behind the dropout. A survey was completed by 624 students belonging to 8 different Spanish universities, rating the factors that could influence them to abandon their studies and those affecting their motivation to continue studying. Non-parametric analyses were performed in order to test the association of motivation as well as self-reported likelihood of dropping out with several variables. According to the research results, 23 of the 40 analyzed factors are correlated with the degree of motivation and 14 factors are correlated with the self-reported probability of dropping out. About 46% of the students declared to have thought about dropping out at some point in the past. Difficulty, followed by bad academic performance and negative relationships with professors are the main reasons for dropping out given by the students. Lack of vocation and distance to their home address were less frequent reasons.